تعلیم و تدریس میں تنظیم اوقات کی اہمیت: قرآن و سنت کی روشنی میں تحقیقی جائزہ: The Importance of Time Management in Teaching and Learning: An Analytical Study in the Light of the Quran and Sunnah - Kashmala; Dr. Saima Farooq (jihat-ul-islam, 2025)
Time is one of the most valuable blessings emphasized repeatedly in Islamic teachings. The Qur’an and Sunnah provide profound guidance on the significance of time, its proper utilization, and the consequences of wasting it. This research paper explores the importance of time management in the field of education and teaching, highlighting its impact on academic success, discipline, and character development. It investigates how organized time allocation enhances the quality of teaching and learning by promoting systematic planning, goal setting, and punctuality. The study analyzes relevant Qur’anic verses and prophetic traditions that encourage the believers to value time, make the most of every moment, and stay accountable for their actions. In the context of education, the paper underscores that both teachers and students must adhere to a disciplined schedule to maximize productivity and spiritual growth. Effective time management contributes not only to academic excellence but also to the holistic development of learners, fostering a sense of responsibility, self-regulation, and respect for others’ time. Additionally, the research emphasizes that contemporary educational institutions should integrate Islamic principles of time organization into their operational strategies. Doing so can help nurture a generation that excels both in knowledge and character. The study concludes that time management, rooted in divine guidance, is essential for building a purposeful, disciplined, and successful educational environment.